PERBANDINGAN FRAMING MEDIA ONLINE DALAM PEMBERITAAN TARIF IMPOR AMERIKA SERIKAT TERHADAP INDONESIA - Akmal, Fitria; Isma, Yuli Santri; KN, Jamiati; Chairunnisak, Syarifah; Kardiati, Depita; Fadhillah, Sarrah Kurnia (Program Studi Komunikasi dan Penyiaran Islam, 2025)
The United States' import tariff policy against Indonesia in 2025 has sparked diplomatic dynamics and public debate, particularly after President Donald Trump announced a tariff reduction from 32% to 19%, accompanied by Indonesia's commitment to purchase Boeing aircraft, energy, and agricultural commodities from the United States. This study aims to compare the news framing of this policy in four national online media outlets: Kompas.com, Liputan6.com, CNBC Indonesia, and CNN Indonesia. The method used is Robert N. Entman's framing analysis, focusing on four framing elements: defining problems, diagnosing causes, making moral judgments, and suggesting remedies. The results show differences in perspective: Liputan6.com emphasizes diplomatic achievements, CNBC Indonesia links tariff reductions to trade-offs regarding purchasing obligations, Kompas.com emphasizes risks to industry and trade imbalances, while CNN Indonesia highlights four conditions for policy implementation. The study's conclusion confirms that media use framing to direct public interpretation, ranging from policy legitimacy to criticism of sovereignty, and confirms the relevance of Entman's model for analyzing political-economic issues in Indonesia